Diagnosing Stagnant Gas Bubbles in a Polymer Electrolyte Membrane Water Electrolyser Using Acoustic Emission - Maier, Maximilian; Meyer, Quentin; Majasan, Jude; Owen, Rhodri E.; Robinson, James B.; Dodwell, James; Wu, Yunsong; Castanheira, Luis; Hinds, Gareth; Shearing, Paul R.; Brett, Dan J. L. (Frontiers in Energy Research, 2020)
The use of acoustic emission as a low-cost, non-destructive, and operando diagnostic tool has been demonstrated for a range of electrochemical energy conversion and storage devices, including polymer electrolyte water electrolysers (PEMWEs) and fuel cells. In this work, an abrupt change in acoustic regime is observed during operation of a PEMWE as the current density is increased from 0.5 A cm-2 to 1.0 A cm-2. This regime change is marked by a sudden drop in the number of acoustic hits, while hit duration, amplitude, and energy increase significantly. It is found that the change in acoustic regime coincides with a significant extension of the stagnant bubble region in the flow channels of the PEMWE, observed with high-speed optical imaging. These results demonstrate that acoustic emission can be used effectively as an operando diagnostic tool to monitor bubble formation (two-phase flow conditions) in PEMWEs, facilitating rapid testing or prototyping, and contributing to operational safety.